Miniature stub-loaded monopole antenna at 800 MHz for FSR sensor / Muhammad Norhisham Abdul Majid - Abdul Majid, Muhammad Norhisham (2014)
In this research, it presents a design simulation and analysis of miniature stubloaded omni-directional monopole antenna at 800 MHz for Forward Scattering Radar (FSR) sensor. A miniature technique and a robust genetic algorithm optimizer have been introduced to minimize the total length of the antenna compares to a standard monopole antenna at same frequency. A. target to achieve desired design goals or performance of the miniature stub-loaded monopole antenna has been set in this project. The desired design goals arise from comparing to commercial off-the-shelf (COTS) antenna that is currently exists in the market at the same frequency. A significant difference in performance between one and two stub-loaded monopole antenna have been observed. The proposed design also shows a 12% smaller in length compared to a standard monopole antenna. A better performance also has been observed but with gain less than 2 dBi. No significant change in gain performance was observed when parameter sweeps analysis was applied to each segments two stub-loaded monopole antenna structure. By simulating on a larger ground plane, an improvement of almost 27% smaller in total length has been achieved with gain improved to 5.24 dBi by the proposed design.